The relationship between visceral obesity and hepatic steatosis measured by controlled attenuation parameter - Lee, Hye Won (PLoS One, 2017)
BACKGROUND: Nonalcoholic fatty liver disease (NAFLD) is closely related with obesity. However, obese subjects, generally represented by high BMI, do not always develop NAFLD. A number of possible causes of NAFLD have been studied, but the exact mechanism has not yet been elucidated. METHODS: A total of 304 consecutive subjects who underwent general health examinations including abdominal ultrasonography, transient elastography and abdominal fat computed tomography were prospectively enrolled. Significant steatosis was diagnosed by ultrasonography and controlled attenuation parameter (CAP) assessed by transient elastography. RESULTS: Visceral fat area (VFA) was significantly related to hepatic steatosis assessed by CAP, whereas body mass index (BMI) was related to CAP only in univariate analysis. In multiple logistic regression analysis, VFA (odds ratio [OR], 1.010; 95% confidence interval [CI], 1.001–1.019; P = 0.028) and triglycerides (TG) (OR, 1.006; 95% CI, 1.001–1.011; P = 0.022) were independent risk factors for significant hepatic steatosis. The risk of significant hepatic steatosis was higher in patients with higher VFA: the OR was 4.838 (P<0.001; 95% CI, 2.912–8.039) for 100<VFA≤200 cm(2) and 7.474 (P<0.001; 95% CI, 2.462–22.693) for VFA >200 cm(2), compared to patients with a VFA ≤100 cm(2). CONCLUSIONS: Our data demonstrated that VFA and TG is significantly related to hepatic steatosis assessed by CAP not BMI. This finding suggests that surveillance for subjects with NAFLD should incorporate an indicator of visceral obesity, and not simply rely on BMI.